Drug and gene delivery to the central nervous system for neuroprotection : nanotechnological advances - Sharma, H. S.; Mureșanu, Dafin; Sharma, Aruna (Springer, 2017)
This book summarizes the latest research on drug and gene delivery to the central nervous system (CNS). The chapters address safety concerns regarding the nanotechnology that is needed to develop nanomedicine for clinical practice. Particular focus is given to new technologies that have emerged in recent years to deliver therapeutic materials, such as genes, drugs, and other agents using nanotechnologies of diverse origin. This is an ideal book for students, teachers, researchers, and clinicians interested in a deeper understanding of nanotechnological advances in therapeutic medicine. This book also: Broadens readers' understanding of viral vector gene delivery to the brain for treating neurogenetic diseases as well as targeted gene delivery into the brain using microbubble-facilitated focused ultrasound Covers in detail the latest developments in delivering therapeutic materials, such as siRNA delivery to the brain for treating neurological diseases, neuroprotective effects of gelatin nanoparticles in stroke, and nanowired drug delivery for brain diseases, heat stroke, and CNS injury Enriches understanding of new technologies for delivering therapeutic materials treating Alzheimer's Disease, including targeted nanodrug delivery through the blood-brain barrier and the superior neuroprotective effects of nanowired drug delivery in Alzheimer's Disease.